ORTODOKSI PESANTREN DALAM TAFSIR AL-BAYĀN KARYA KH. SHODIQ HAMZAH SEMARANG - Zulaikhah Fitri Nur Ngaisah (UIN Siber Syekh Nurjati Cirebon, 2025)
Tafsir al-Bayān is a Qur’anic exegesis that emerged and was written by a pesantren (Islamic boarding school) scholar, Shodiq Hamzah. It is acknowledged that this work extensively refers to Qur’anic commentaries authored by earlier scholars. At this point, it is possible that he integrates, to some extent, the teachings of classical scholars, which indirectly positions his work as a Qur’anic exegesis with an orthodox paradigm. Orthodoxy itself refers to the preservation of religious understanding inherited from previous generations through interconnected scholarly transmission. This research aims to uncover the pesantren orthodoxy paradigm in Tafsir al-Bayān, as it was written by a productive pesantren figure and has been followed by the local community. The method employed is descriptive-analytical, using a content analysis approach directed at Tafsir al-Bayān, particularly focusing on its sources of reference and theological thought. To identify orthodoxy, this study applies five concepts of doctrinal orthodoxy proposed by John B. Henderson. The findings of this research affirm that Shodiq Hamzah’s Tafsir al-Bayān demonstrates an orthodox tendency due to its commitment to the works of earlier scholars (al-kutub al-muʿtabarah) and the opinions of the salaf as primary sources of reference. His scholarly background and Sunni scholarly networks also contribute to constructing this orthodox framework of thought. Furthermore, the orthodoxy of Shodiq Hamzah’s interpretation reinforces pesantren traditions, particularly in matters of theology (kalām) affiliated with Ahl al-Sunnah wa al-Jamāʿah. Nevertheless, his interpretation has not yet elaborated on contemporary discourses, resulting in an impression of conservatism and indicating the need for a more comprehensive interpretation to address contemporary problems. Tafsir al-Bayān adalah sebuah tafsir al-Qur’an yang ditulis oleh tokoh pesantren, Shodiq Hamzah. Karya ini diketahui banyak merujuk pada tafsir al-Qur’an karya ulama terdahulu, sehingga memungkinkan adanya integrasi ajaran dari generasi sebelumnya yang menjadikannya sebagai tafsir yang berparadigma ortodoks. Ortodoksi di sini merujuk pada upaya mempertahankan pemahaman agama yang diturunkan secara berkesinambungan melalui tradisi keilmuan yang saling terkait. Penelitian ini bertujuan untuk menelusuri paradigma ortodoksi pesantren dalam Tafsir al-Bayān, mengingat penulisnya adalah tokoh pesantren yang produktif dan karyanya banyak diikuti masyarakat setempat. Metode yang digunakan adalah deskriptif-analisis dengan pendekatan content analysis, berfokus pada sumber rujukan dan pemikiran teologis dalam tafsir tersebut. Untuk mengidentifikasi ortodoksi, penelitian ini menggunakan lima konsep ortodoksi menurut John B. Henderson. Hasil penelitian menunjukkan bahwa Tafsir al-Bayān memiliki kecenderungan ortodoks yang ditandai dengan komitmen penulisnya pada karya ulama terdahulu (al-kutub al-mu’tabarah) dan pendapat ulama salaf sebagai sumber utama. Latar belakang keilmuan dan jaringan keulamaan Sunni turut membentuk kerangka pemikiran ortodoks tersebut. Selain itu, ortodoksi tafsir Shodiq Hamzah memperkuat tradisi pesantren, khususnya dalam ranah teologi atau kalam yang berafiliasi dengan Ahl al-Sunnah wa al-Jamā‘ah. Meski demikian, tafsir ini belum banyak menanggapi diskursus kontemporer, sehingga menimbulkan kesan konservatif dan memerlukan interpretasi lebih komprehensif untuk menjawab persoalan kekinian.